Using Inquiry learning Method and Ladder Snake Game to Teach Reading Skills for The 7th Grade Students of SMPN 1 Kartoharjo - Muhammad Azka Fahmi; Sumani Sumani; Fitra Pinandhita (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
: This research explores the implementation of